Neuromechanics of Coordination during Swallowing in Aplysia californica - Ye, Hui (J Neurosci, 2006)
Bernstein (1967) hypothesized that preparation of the periphery was crucial for correct responses to motor output. To test this hypothesis in a behaving animal, we examined the roles of two identified motor neurons, B7 and B8, which contribute to feeding behavior in the marine mollusk Aplysia californica. Neuron B7 innervates a hinge muscle and has no overt behavioral effect during smaller-amplitude (type A) swallows, because the hinge muscle is too short to exert force. Neuron B8 activates a muscle (I4) that acts solely to grasp material during type A swallows. During larger-amplitude (type B) swallows, the behavioral actions of both motor neurons change, because the larger-amplitude anterior movement of the grasper sets up the periphery to respond differently to motor outputs. The larger anterior movement stretches the hinge muscle, so that activating neuron B7 mediates the initial retraction phase of swallowing. The changed position of the I4 muscle allows neuron B8 not only to induce grasping but also to pull material into the buccal cavity, contributing to retraction. Thus, larger-amplitude swallows are associated with the expression of two new degrees of freedom (use of the hinge to retract and use of the grasper to retract) that are essential for mediating type B swallows. These results provide a direct demonstration of Bernstein's hypothesis that properly positioning the periphery can be crucial for its ability to correctly respond to motor output and also demonstrate that biomechanical context can alter the functions of identified motor neurons.